Radikalisme Islam dalam Representasi Media di Thailand - Muhammad Fahmi (Al-Ulum, 2016)
This article intends to look at how Islamic radical (ISIS) is represented in the Thai media. The method used in this study is critical discourse analysis method proposed by Theo van Leuwen which focuses on how actors in the inclusion and exclusion in the news media. This study concluded on: first, The Bangkok Post, represents ISIS identical and just as dangerous as Muslim rebels in southern Thailand. ISIS issue be a way to marginalize the Muslim rebels in southern Thailand region of the country bordering the Malay Peninsula. Second, the Pattaya Mail purposely did not link the issue of ISIS in southern Thailand among the Muslim fighters because they would only weaken efforts to build integration and large associations vis a vis ISIS. Pattaya Mail prefers macro strategy, which attempts to include as many friends to confront a common enemy: ISIS